Dalita yuvāoṃ ke parivartī dr̥ṣṭikoṇa - Rāṭhaura, Jagadīśa Siṃha (Sumana Prakāśana, 1994)
Changes in the socioeconomic status and values of the youth belonging to the lower classes in the context of reforms undertaken in post-independence India; study of the Moradabad District, Bijnor District, and Rāmpur District in Uttar Pradesh